2012
DOI: 10.1016/j.bandl.2012.04.014
|View full text |Cite
|
Sign up to set email alerts
|

The neural bases of difficult speech comprehension and speech production: Two Activation Likelihood Estimation (ALE) meta-analyses

Abstract: The role of speech production mechanisms in difficult speech comprehension is the subject of on-going debate in speech science. Two Activation Likelihood Estimation (ALE) analyses were conducted on neuroimaging studies investigating difficult speech comprehension or speech production. Meta-analysis 1 included 10 studies contrasting comprehension of less intelligible/distorted speech with more intelligible speech. Meta-analysis 2 (21 studies) identified areas associated with speech production. The results indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
129
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(141 citation statements)
references
References 85 publications
12
129
0
Order By: Relevance
“…In this same paper, the authors examined the effective connectivity between these areas during speech production and concluded that the insular cortex may function as a relay between the cognitive aspects of language analyzed in BA 44 and the motor preparation for vocalization in basal ganglia and cerebellum. This finding was later supported by activation likelihood estimate (ALE) meta-analyses of neuroimaging studies examining normal speech production and the comprehension of distorted speech (Adank, 2012). Left anterior insula was associated with speech production; however, bilateral anterior insulae activations were associated with distorted speech comprehension suggesting increased insular recruitment during difficult speech-language processing.…”
Section: Introductionmentioning
confidence: 58%
“…In this same paper, the authors examined the effective connectivity between these areas during speech production and concluded that the insular cortex may function as a relay between the cognitive aspects of language analyzed in BA 44 and the motor preparation for vocalization in basal ganglia and cerebellum. This finding was later supported by activation likelihood estimate (ALE) meta-analyses of neuroimaging studies examining normal speech production and the comprehension of distorted speech (Adank, 2012). Left anterior insula was associated with speech production; however, bilateral anterior insulae activations were associated with distorted speech comprehension suggesting increased insular recruitment during difficult speech-language processing.…”
Section: Introductionmentioning
confidence: 58%
“…A strikingly consistent pattern of functional imaging results from speech-recognition studies is elevated cingulo-opercular activity, particularly when speech recognition is difficult (Sharp et al, 2006;Eckert et al, 2009;Harris et al, 2009;Adank, 2012;Wild et al, 2012;Erb et al, 2013). Our findings demonstrate that cingulo-opercular engagement increases the likelihood of correct word recognition on the next trial, which is consistent with sim- ilar findings in visuospatial studies (Kerns et al, 2004;Weissman et al, 2006).…”
Section: Discussionmentioning
confidence: 96%
“…Specifically, lower FA values were seen in the left anterior IFOF for the oldest adults with stronger visual cortex effects. This association was primarily driven by reduced linearity of diffusion tensors, which can be affected by the density of axon membranes (Alexander et al, 2000;Beaulieu, 2002;Mori and Zhang, 2006). Therefore, age-related declines in the ability to maintain attention (Lustig et al, 2001;Tun et al, 2009) during speech recognition in noise are predicted to stem, at least in part, from IFOF declines.…”
Section: Discussionmentioning
confidence: 99%
“…We interpret the relatively large number of cingulo-opercular results from speech production and perception studies with challenging listening conditions (Adank, 2012) as evidence that language tasks can elicit domain general adaptive control functions. Elevated cingulo-opercular BOLD responses also have been observed in aphasia patients with better language task performance, raising important questions about the contribution of adaptive control and language networks (Geranmayeh et al, 2014a).…”
Section: Discussionmentioning
confidence: 99%